PROBLEMS OF EFFECTIVE USE OF ELECTRICAL ENERGY IN AGRICULTURE AND WATER MANAGEMENT - Yulchiev Mash'albek Erkinovich; Rahmatullaev Shamsiddin Hakimboy ugli (Лучшие интеллектуальные исследования, 2024)
Abstract: During the transition to the market economy, factories for the processing of agricultural products are being established. New technologies and technical tools are widely used in breeding livestock and agricultural products, the number of microclimate-creating and auxiliary electrified devices in residential areas and the household sector is increasing.